Do Ligamentum Teres Tears Portend Inferior Outcomes in Patients With Borderline Dysplasia Undergoing Hip Arthroscopic Surgery? A Match-Controlled Study With a Minimum 2-Year Follow-up. (September 2017) - Chaharbakhshi, Edwin O.; Perets, Itay; Ashberg, Lyall; Mu, Brian; Lenkeit, Christopher; Domb, Benjamin G.
Background: Arthroscopic surgery in borderline dysplastic hips remains controversial, but the role of the ligamentum teres (LT) has not been studied in this setting. Hypothesis: Borderline dysplastic patients with LT tears have worse short-term outcomes than those without LT tears. Study Design: Cohort study; Level of evidence, 3. Methods: Data were prospectively collected on patients who underwent arthroscopic surgery between February 2008 and April 2014. The inclusion criteria were borderline dysplasia (lateral center-edge angle [LCEA], 18°-25°) and labral tears; arthroscopic treatments including labral preservation and capsular plication; and preoperative patient-reported outcome scores including the modified Harris Hip Score (mHHS), Non-Arthritic Hip Score (NAHS), Hip Outcome Score–Sport-Specific Subscale, and visual analog scale for pain. Patients were excluded for preoperative Tönnis osteoarthritis grade >0, workers' compensation claims, previous ipsilateral hip surgery and conditions, or frank dysplasia (LCEA <18°). Patients with LT tears were pair-matched to patients without tears for sex, age at surgery ±10 years, body mass index (<30 kg/m 2 vs ≥30 kg/m 2 ), labral treatment type, and microfracture. Results: Of 68 eligible patients, 63 (93%) had a minimum 2-year follow-up, and 30 (48%) had LT tears. Twenty patients in each group were pair-matched. The mean follow-up time was 54.3 months (range, 24.2-83.8 months) for the LT tear group and 38.6 months (range, 24.6-70.6 months) for the control group ( P = .002). Ninety percent were female. There were no significant differences regarding demographics or intra-operative procedures. The LT tear group trended toward lower postoperative mHHS ( P = .09) and NAHS ( P = .09) values. Mean satisfaction was 8.1 for the LT tear group and 7.9 for the control group. Preoperative and follow-up scores were not significantly different between the groups. The LT tear group had 5 revisions, with 1 revision in the control group. Three patients (15%) in the LT tear group underwent total hip arthroplasty (THA); no patients in the control group required THA. Conclusion: In borderline dysplastic patients undergoing hip arthroscopic surgery with labral treatment and capsular plication, LT tears may indicate advanced instability and portend slightly inferior outcomes when compared with a match-controlled group. Borderline dysplastic patients with LT tears may have increased propensities toward revision arthroscopic surgery and conversion to THA. LT tears in these patients may warrant consideration for additional procedures including periacetabular osteotomy and LT reconstruction.